중고거래 어플리케이션 〈당근마켓〉 리뷰텍스트에 나타난 소비자의 인성 함축단어 텍스트마이닝 분석 - 정예린(Yea-Rin Jung); 주영애(Young-Ae Ju) (한국콘텐츠학회 논문지, 21(11), 2021)
This study analyzes the use and meaning of consumer personality implication words in the review text of the Used Transaction Application <Daangn Market>. From of May 2021, the data were collected for the past six months by our Web crawler in Seoul and Gyeonggi Province, and a total of 1368 cases were collected first by random sampling, and finally 570 cases were preprocessed. The results are as follows. First, 48.2% of review texts were related to the personality of consumers even though it was a commercial platform of products. Second, the review text is mainly positive, which formed a text network structure based on the keyword 'gratitude'. Third, the review text, which implies consumer character, was divided into two groups: 'extrovert personality' and 'introvert personality' of consumers. And the individuality of the two groups worked together on the platform. In conclusion, we would like to suggest that consumer personality plays an important role in the platform transaction process, that consumer personality will play a role in the services of the platform in the future, and that consumer personality should be studied from various perspectives. 본 연구는 중고거래 어플리케이션 <당근마켓>의 리뷰텍스트에 나타난 소비자의 인성 함축단어의 사용실태를 분석하였다. 데이터 수집은 2021년 5월로부터 과거 6개월간 서울과 경기권을 대상으로 하였다. 이는 웹 크롤러를 개발하여 무작위 추출 총 1368건을 수집 후, 최종 570건을 전처리하여 사용하였다. 결과는 다음과 같다. 첫째, 제품의 상거래 플랫폼임에도 리뷰텍스트의 48.2%는 소비자의 인성 관련 내용이었다. 둘째, 리뷰 텍스트는 긍정적 반응이 주를 이루며 이는 감사라는 키워드를 기반으로 텍스트 네트워크 구조를 형성하였다. 셋째, 소비자 인성을 함축하는 리뷰 텍스트는 소비자의 '대타적 인성'과' 대내적 인성'으로 그룹화되었고, 이는 플랫폼에서 통합적으로 작용하였다. 결론적으로 인성 관련 요인들이 플랫폼 거래 과정의 상호작용에서 중요한 역할을 함을 확인하였고, 앞으로 플랫폼의 서비스 품질에도 소비자의 인성이 경쟁력으로 작용할 것이므로, 이에 대해 다각도에서 연구되어야 할 것임을 제언하였다.